International migration and the change of women's position among left behind in rural Bangladesh - Hadi, Abdullahel (BRAC Research and Evaluation Division (RED), 2019)
While the impact of remittances on the economic condition of sending communities has received much attention, the effects of international migration on women's position among the left: behind have not been adequately explored. This paper examines the changes of the left behind women's position at the family level as a result of the migration of adult men to overseas. Data came from a demographic surveillance system covering 70 villages in Bangladesh. All migrant families having at least one male member working abroad for more than six months were identified in the study villages in 1996. A comparable number of non-migrant families were selected at random from the same villages to yield a total sample of 1,030 families. In-depth interviews were conducted with adult women of the sample families. Findings reveal that the overseas migration of adult males has a significant positive association with women's decision making capacity and education of girls in the migrant families. The remittances as well as the influence of secular values have reduced the practice of dowry in marriages. Multivariate analysis suggests not only that remittances have increased the financial capacity of the migrant families, but also that secular influences from overseas might have modified women's position when the role of other socio-economic factors are controlled. The study concludes that overseas migration of adult men can create a context for change of women's position in the traditional communities.